Young pioneers - Lane, Rose Wilder 1886-1968. (New York McGraw-Hill, 1976)
After getting married and settling at Wild Plum Creek, David's and Caroline's lives are turned upside down when disaster strikes and David must go east to find work for the winter.
First published under title: Let the hurricane roar.
Keywords: Frontier and pioneer life -- Minnesota -- Fiction; Family life -- Minnesota -- Fiction; Minnesota -- Fiction